GERM-04. MANAGEMENT OF CNS GERM CELL TUMORS: EXPERIENCE FROM SUN YAT-SEN UNIVERSITY CANCER CENTER - Guo, Chengcheng (Neuro Oncol, 2018)
Primary CNS germ cell tumors (CNS-GCTs) are a group of heterogeneous tumors, and comparative higher incidence in Asian countries. Here we present our institutional experience for CNS-GCTs treatment. There are 209 CNS-GCTs cases treated at Sun Yat-sen University Cancer Center during last 15 years. The median age of patients was 16 years old (4-69 y-old). The tumors were classified as Germinoma and Nongerminoma germ cell tumors(NG-GCTs), and also secretory sub-type(AFP≥10 ng/dL and/or β-HCG)≥50 IU/L) or non-secretory sub-type(normal level of tumor marker). There were 60 cases received Ventricle-peritoneal shunt (V-P shunt) or endoscopic third ventricle colostomy due to obstructive hydrocephalus. Treatment modality including: comprehensive treatment 84cases (40.2%), ie chemotherapy plus radiation therapy (some cases with chemo-Radio-chemo Sandwich Therapy) with or without surgical intervention; Monotherapy, ie Chemotherapy only:37 (17.7%), Radiotherapy Only:13 (6.2%). Surgery for tumor removal or biopsy:55cases (25.4%), in which 4 cases were failed from initial diagnostic chemotherapy. There were also some patients(about 6%) received Gamma knife radiosurgery. The 5 years overall survival(OS) rate was better for those with comprehensive treatment, compared those with monotherapy cases: 86.5% vs 66.7%. The 5 ys OS rate according tumor markers was also different: Non Secretory Subtype:79.8%,HCG increased Subtype: 92.9%, AFP increased Subtype: 64.8%, and AFP+HCG coincreased Subtype: 75.0%. Conclusion from our institutional experience: Although smaller number of patients need surgical tumor removal, clinical diagnosed CNS-GCT (without histological confirmation) patients may obtain good responses when receiving comprehensive treatments of chemotherapy combined with radiotherapy.